Hepatitis B virus haplotype number at baseline is a predictive marker of functional cure during antiviral therapy for patients with genotypes A and D HBeAg‐positive chronic hepatitis B. Issue 5 (25th November 2022) - Wagner, Josef; Yuen, Lilly; Littlejohn, Margaret; Sozzi, Vitina; Jackson, Kathy; Martin, Ross; Aeschbacher, Thomas; Suri, Vithika; Tan, Susanna K.; Feierbach, Becket; Gaggar, Anuj; Marcellin, Patrick; et al.
Summary: Backgrounds and Aims: We investigated associations between hepatitis B virus (HBV) genome‐length haplotype number (HN) at baseline in subjects with HBeAg‐positive chronic hepatitis B (CHB), and the likelihood of achieving functional cure during direct‐acting antiviral therapy Method: We analysed 86 HBeAg‐positive baseline samples from patients with HBV genotypes A and D who were enrolled in a Phase II trial of tenofovir disoproxil fumarate (TDF) to determine if HN was a biomarker of HBsAg loss during therapy. Findings were validated using baseline samples from 181 patients with HBV genotypes A and D from an independent clinical trial utilising TDF or tenofovir alafenamide therapy in HBeAg‐positive CHB. Results: In the HBeAg‐positive test cohort, patients with genotypes A or D and ≤2 haplotypes had a minimum of 21‐fold higher likelihood of achieving HBsAg loss on TDF. Baseline HN ( p  < 0.0001) was a stronger predictor of HBsAg loss on therapy than HBsAg titre ( p  = 0.03), HBeAg titre ( p  = 0.0002), or the presence of HBV basal core promoter (A1762T, p  = 0.0379 and G1764A, p  = 0.0176) or G1896A precore mutations ( p  = 0.0218). This finding was validated in the independent validation cohort. HN was statistically higher in patients with HBV genotypes B or C infection compared to genotypes A and D. Conclusion: Baseline HN ≤2 predicts which patients with HBV genotypes A or D will more likely progress to functional cure on current direct‐acting antiviral therapy, with greater accuracy than current biomarkers including baseline HBsAg and HBeAg titre. Abstract : Hepatitis B virus (HBV) haplotype number ≤2 predicts HBV genotype A and D patients who will, or will not achieve HBsAg loss on direct acting antiviral therapy